EXPLORING Z GENERATION ATTITUDES TOWARD VARIETIES OF ENGLISH(ES) - Aisy, Laela Rohadatul; Wahyudi, Ribut (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
English, one of the most dominant languages, has undergone transformations and divergences that have created a variety of variations in different parts of the world. The fact is that English has more than 160 acknowledged variations of accents across the globe. Each variation from standard English to a distinctive local reflects its unique culture and history. This study aims to investigate Generation Z's attitudes towards variations of Englishes of their English as foreign language communication experiences. This research adopted qualitative research benefiting from Saraceni's (2010) Space, Culture, Ideology and Psychology (SCIP) model to understand variety of English(es). Four English literature students were selected as respondents when they were still in their 7th semester and aged 21-22 at an Islamic university (under Ministry of Religious Affairs) in East Java, Indonesia. The results revealed that the dominance of American English is still the benchmark in most participants' preferences. A number of competing and interconnected factors such as habits, motivations, and practices with the influence of family, social, educational, and environmental factors shape their preferences on English(es) varieties. The participants showed positive, contradictory attitudes (positive and negative) to negative attitude towards the varieties of Englishes.